Reliability and Validity of the Agility Test for Adults Test in Primary and Secondary School Students - Carballo-Afonso, Rocío; González-Devesa, Daniel; Sanchez-Lastra, Miguel Adriano; Diz-Gómez, José C; Ayán-Pérez, Carlos (Journal of strength and conditioning research, 2025)
Carballo-Afonso, R, González-Devesa, D, Sanchez-Lastra, MA, Diz-Gómez, JC, and Ayán-Pérez, C. Reliability and validity of the agility test for adults test in primary and secondary school students. J Strength Cond Res 39(6): e758-e763, 2025-This study aimed to identify the reliability and validity of the Agility Test for Adults (ATA) among primary and secondary school students. A sample comprised 156 primary and 289 secondary students. Anthropometric variables, Agility Test for Adults, and results from the 10 × 4-m shuttle run test of all subjects were analyzed. Higher internal consistency values were observed for the Agility Test for Adults ( α : 0.82-0.88). Test-retest reliability values were fair for both the Agility Test for Adults original (intraclass correlation coefficient [ICC]: 0.733; 95% confidence interval (CI) [0.579-0.821]) and adjusted performance time (ICC: 0.754; 95% CI [0.573-0.845]). A fair significant association between both the Agility Test for Adults original (Rho = 0.46-0.48) and adjusted (Rho = 0.46-0.49) performance time and 10 × 4-m shuttle run test were found. This association were fair for primary (Rho = 0.37-0.43) and secondary students (Rho = 0.41). Agility Test for Adults demonstrated fair relative reliability, good absolute reliability, and fair convergent validity when conducted by school students. The properties of the Agility Test for Adults make it highly suitable for the early and cost-effective detection of developmental motor delays in childhood. In addition, the Agility Test for Adults can aid in the design of tailored exercise programs aimed at enhancing coordination and physical performance, which is essential for the optimal development of motor skills in children and adolescents.